2022
DOI: 10.1111/sdi.13125
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting quality of daytime and nighttime sleep among dialysis patients: A single center experience

Abstract: Background: Hemodialysis is the most common treatment modality for patients with chronic kidney disease (CKD). Excessive daytime sleepiness and poor nighttime sleep is a common problem among these patients. Patients on maintenance hemodialysis (MHD) are regularly exposed to impaired fluid balance, which may cause overhydration of varying degree. However, the role of hydration status in sleep quality has not been explored in Indian setting. Hence, this study was undertaken to assess the factors affecting sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Numerous studies have shown that RLS can also be considered a sleep disorder [ 35 ]. Indeed, the sleep quality of MHD patients also showed varying degrees of decline [ 36 ]. Based on this evidence, the evaluation of sleep quality is also an important evaluation indicator for the beneficial effect of LIPC on RLS improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that RLS can also be considered a sleep disorder [ 35 ]. Indeed, the sleep quality of MHD patients also showed varying degrees of decline [ 36 ]. Based on this evidence, the evaluation of sleep quality is also an important evaluation indicator for the beneficial effect of LIPC on RLS improvement.…”
Section: Discussionmentioning
confidence: 99%